Global Trends of Landfill Leachate Treatment Research: A Bibliometric Analysis During 2000-2020 - Mohammad Reza Sabour; Shamimeh Babaei Khorzoughi; Saman Moftakhari Anasori Movahed (Environmental Energy and Economic Research, 2021)
Landfill leachate is heavily contaminated and consists of high amount of organic compounds, toxic gases, inorganic salts, halogenated hydrocarbons, and heavy metals that exerts a serious threat to public health and the environment. Therefore it requires treatment before direct discharge into water bodies. Although landfill leachate treatment has been studied by many researchers, lacking comprehensive review in this area can be considerable. This paper aims to assess the trend of landfill leachate treatment research and to show the related hotspots through conducting a bibliometric analysis, based on 3523 publications from Web of Science during 2000-2020. Various significant aspects including document type, publications growth trends, key countries/territories, subject categories, major journals, and keywords co-occurrence, were all systematically analyzed in this paper. Also, VOS viewer has been employed to evaluate the collaboration of countries/territories and keywords. Based on the results, the growing number of publications related to landfill leachate treatment over the last 20 years, demonstrate significant growth trends of the research. According to the subject category analysis, the most dominant categories were Environmental Sciences and Environmental Engineering with more than 60% contribution. “Waste Management” is the most productive journal followed by “Journal of Hazardous Materials”, “Desalination and Water treatment”, and “Water Science and Technology”. China is the leading country in contribution to the total number of publications followed by the USA and Malaysia. Moreover, to identify the pioneer countries, keyword clustering analysis was conducted and it demonstrated that the number of landfill leachate-related publications have significantly increased during the studied period.